Intrahepatic biliary strictures after liver transplantation are morphologically similar to primary sclerosing cholangitis but immunologically distinct - Zhou, Taotao; Bartelheimer, Katja; Ruping, Fabian; Rupp, Christian; Sauer, Peter; Koschny, Ronald; Mehrabi, Arianeb; Mieth, Markus; Haken, Rebecca von; Weiss, Karl Heinz; Gotthardt, Daniel; Rauber, Conrad (European journal of gastroenterology & hepatology, 2020)
Objective Biliary strictures are an important cause of morbidity and mortality in primary hepatic disease and after liver transplantation (LT). We aimed to characterize inflammatory cytokines in biliary fluids in biliary strictures to investigate their immunological origin. Methods We conducted a retrospective study on 72 patients with strictures after LT, eight patients with primary sclerosing cholangitis (PSC) and 15 patients with secondary sclerosing cholangitis (SSC). We measured cytokines interleukin (IL)-2, -4, -6, -10, -17, monocyte chemoattractant protein (MCP)-1, fibroblast growth factor (FGF)-2 and interferon (IFN)-gamma as well as biochemical components such as protein and phospholipids in biliary fluid obtained from endoscopic retrograde cholangiography (ERC). Cell viability assays were performed on human cholangiocytes (H69) after being treated with IL-6, IL-4 and IFN-gamma. Results Bile of patients with diffuse strictures after LT or due to SSC showed low values of all measured cytokines except for IL-6 levels, which were largely elevated in patients with diffuse strictures after LT. Patients high in biliary IL-6 showed an increase in profibrotic markers FGF-2 and MCP-1. In contrast, PSC bile was dominated by a Th1/Th17 profile with elevated IL-2, IL-17 and IFN-gamma. In LT patients with biliary strictures, biliary IL-6 negatively predicted retransplantation-free survival after ERC. Conclusion PSC patients showed a biliary Th1/Th17 cytokine profile, while SSC and diffuse strictures showed low values of cytokines except IL-6. In diffuse intrahepatic strictures after LT, biliary IL-6 is strongly associated with retransplantation-free survival after ERC.
Gesehen am 16.06.2020